Discrepancies in the caloric testing and video Head Impulse Test results in a case with bilateral lateral semicircular canal malformations. Issue 3 (June 2023) - Fujiwara, Keishi; Morita, Shinya; Fukuda, Atsushi; Hoshino, Kimiko; Nakamaru, Yuji; Homma, Akihiro
Abstract: Lateral semicircular canal (LSCC) malformations represent one of the most common types of inner ear malformation. As many cases of LSCC malformations are asymptomatic, detailed vestibular functions in such cases remain unclear. We present a case with bilateral LSCC malformations for whom the function of each vestibular organ was evaluated by caloric testing, video Head Impulse Test (vHIT) and vestibular evoked myogenic potentials (VEMP). Caloric testing showed canal paresis of the left side, whereas vHIT showed bilateral normal semicircular canal function. The results of VEMP indicated left saccular dysfunction. Discrepancies in caloric testing and vHIT results were observed and these discrepancies are thought to be due to endolymphatic hydrops rather than vestibular hypofunction, similar to that in Meniere disease.